Strategi Marketing Communication melalui Event Energizing the Acceleration 67th PT. Pertamina Persero dalam Meningkatkan Brand Image IHC Klinik Pertamina - Fharhan Fadhlurrahman; Nita Noviati; Eka Harrdi Yudharsa (IAI Nasional Laa Roiba Bogor, 2025)
This study analyzes the marketing communication strategy implemented in the